FIRST RECORD OF THE ENTOMOPATHOGENIC NEMATODE OSCHEIUS TIPULAE (LAM AND WEBSTER, 1971) IN IRAQ - TAHER, KAYFI SIDQI; HASSAN, FEYROZ RAMADAN (Journal of Duhok University, 2023)
Oscheius tipulae, first described by Lam and Webster 1971, is one of the entomopathogenic, inhabiting soil nematodes and is very common in the soil of many regions of the world. O. tipulae was isolated from soil samples collected from olive and grapevine trees (Summel district, Duhok province, Kurdistan Region - Iraq) using galleria bait traps. Molecular identification based on ITS-rDNA gene was done to identify the samples. Using blast search, a homology of (98%) was exhibited to the O. tipulae which is the first record of this species in Iraq